PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KAYAWAN (STUDI PADA BADAN PENANGGULANGAN BENCANA KOTA SEMARANG - Amalia do Rosario da Costa, 10.05.51.0079; Sutomo, Yohanes (Students Journal of Economic and Management, 2014)
Work motivation that grows from within high employee will improve performance and job satisfaction in completing a job. And higher employee motivation in completing the work it will improve performance and employee satisfaction. This study aimed to analyze the effect of variable motivation and job satisfaction on employee performance. The sample used in this study were 62 respondents, object of research that will be used in this research is Semarang Disaster Management Agency. The type of data used is primary data. Methods of data collection in this study was through koesioner. Analysis of the data used include test validity, reliability testing, multiple linear regression, the coefficient of determination and hypothesis testing that includes the F test and t test. Based on data analysis and hypothesis testing showed that in partial motivation (X1) and a significant positive effect on employee performance (Y). Variable Kepuaan work (X2) and no significant negative impact on employee performance (Y). Results of regression analyzes Motivation (X1) positive value of 0.971 and job satisfaction variable is negative for 0.069. The test results are known variables determination and motivation Job satisfaction describes the value of adjusted R square of 0,920 (92%) of the employee performance while the remaining 8% is influenced by other variables that were not analyzed in this study.Keywords: motivation, job satisfaction and employee performance.